You need to remember that the marginal cost expresses the increase or decrease of total cost if one item more is produced.

Since the first derivative depicts the monotony of function, thus you need to differentiate the total cost function with respect to q to find the marginal cost expression such that:

`C'(q) = (60q - 12q^2 + q^3 )'`

`C'(q) = 60 - 12*2*q^(2-1) + 3*q^(3-1)`

`C'(q) = 60 - 24*q + 3*q^2`

**Hence, evaluating expression of marginal cost yields `MC = C'(q) = 60 - 24*q + 3*q^2.` **

For cost as a function of the number of products manufactured C(q), the marginal cost is the derivative of C(q) with respect to q or C'(q)

Here, C(q) = 60q - 12q^2 + q^3

C'(q) = 60 - 24q + 3q^2

**The marginal cost is C'(q) = 60 - 24q + 3q^2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now